CLIMA ORGANIZACIONAL E QUALIDADE DE VIDA DE DOCENTES DO CURSO DE ODONTOLOGIA DE UMA UNIVERSIDADE PÚBLICA - Souza, Josias Soares de (2020)
Introduction: The constant changes in the labor market demand that organizations seek to improve their production. Through this search, organizations realized that they should prioritize their workers, as their knowledge and skills proved to be the great